High Voltage Fence (The Netherlands and Belgium) - Vanneste, Alex (1914-1918-online. International Encyclopedia of the First World War, 2014)
In 1915 the Germans built an electric fence along the Belgian-Dutch border, consisting of three lines of wires which were intended to stop all disturbing border activities that might severely harm the military operations and authority of the occupier.
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Militär